2010
DOI: 10.1088/0953-2048/23/5/054004
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced unconventional superconductivity near a quantum critical point in CaFe2As2

Abstract: 75 As-zero-field nuclear magnetic resonance (NMR) and nuclear quadrupole resonance (NQR) measurements are performed on CaFe2As2 under pressure. At P = 4.7 and 10.8 kbar, the temperature dependences of nuclear-spin-lattice relaxation rate (1/T1) measured in the tetragonal phase show no coherence peak just below Tc(P ) and decrease with decreasing temperature. The superconductivity is gapless at P = 4.7 kbar but evolves to that with multiple gaps at P = 10.8 kbar. We find that the superconductivity appears near … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 48 publications
(103 reference statements)
3
32
0
Order By: Relevance
“…Below T c , 1/T 1 decreases steeply due to the opening of the superconducting gaps. The hump structure at T ∼ 0.4 T c is due to the multiple-gap character as reported for other compounds [4][5][6]8]. The T variation at low T is much stronger than T 3 , and even stronger than T 5 , as can be clearly seen in the figure.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Below T c , 1/T 1 decreases steeply due to the opening of the superconducting gaps. The hump structure at T ∼ 0.4 T c is due to the multiple-gap character as reported for other compounds [4][5][6]8]. The T variation at low T is much stronger than T 3 , and even stronger than T 5 , as can be clearly seen in the figure.…”
supporting
confidence: 76%
“…Previous nuclear-magnetic resonance (NMR) and nuclear-quadrupole resonance (NQR) measurements have found that the superconductivity is in the spin-singlet state with multiple gaps [4][5][6]. Recent systematic measurements on Ba(Fe 1−x Co x ) 2 As 2 [7], CaFe 2 As 2 under pressure [8], LaNiAsO 1−x F x [9], and BaFe 2 (As 1−x P x ) 2 [10] have suggested that the antiferromagnetic spin fluctuation (AFSF) originated from their multiple electronic bands correlates with the appearance of the pertinent superconducting properties. On the other hand, there are also reports suggesting that AFSF is not important to realize high T c .…”
mentioning
confidence: 99%
“…Effective two dimensional electronic structure seem to be essential to achieve high superconducting transition temperature and almost all the superconductors (conventional and unconventional) having high transition temperature possess two dimensional electronic structure. In CaFe 2 As 2 , the higher degree of Ca-As hybridization in collapsed tetragonal phase and the observation of pressure induced superconductivity 35, 5658 appears to be linked. It is to note here that while the non-hydrostatic conditions and doped systems (unit cell becomes too big for doped systems of interests) could not be treated in our calculations, the results presented here provide an understanding of the scenarios involving those issues via providing evidence that application of pressure and/or structural distortions help the system to evolve towards the proximity of quantum criticality via destruction of magnetic long range order and enhancement of the influence of charge reservoir layer in the electronic structure.…”
Section: Discussionmentioning
confidence: 94%
“…Below 160 K, each NMR line for H c axis in the case of "annealed" crystals splits into two lines due to internal field H int (parallel or antiparallel to H) which is produced by the Fe reports [175]. Structural phase transition without any magnetic transition has been established as the cause for this large change in ν Q [177].…”
Section: Nmr Studymentioning
confidence: 95%